Perioperative and long-term outcomes of laparoscopic liver resection for combined hepatocellular carcinoma and cholangiocarcinoma versus intrahepatic cholangiocarcinoma: A propensity score matching analysis - Chengfei Du; Hanyu Wang; Wenli Cao; Zichen Yu; Junwei Liu; Jie Liu; Liming Jin; Yunyun Feng; Fangqiang Wei (PLoS ONE, 2025)
Background Laparoscopic liver resection (LLR) has been increasingly used to treat intrahepatic cholangiocarcinoma (ICC), yet the role of LLR on combined hepatocellular carcinoma and cholangiocarcinoma (cHCC-CC) remains unclear. The purpose of this study was to compare the perioperative efficacy and long-term prognosis of LLR for cHCC-CC and ICC through the use of propensity score matching (PSM) analysis. Methods Clinicopathologic, perioperative, and survival data of patients with cHCC-CC and ICC who underwent LLR from November 2018 to May 2023 at our institution were retrospectively collected. The two groups were further analyzed using 1:1 PSM to compare perioperative outcomes and long-term prognosis. Results A total of 115 patients who underwent LLR for either eHCC-CC or ICC were ultimately included in the study. Among them, there were 24 cases in the cHCC-CC group and 91 cases in the ICC group. After PSM, the cHCC-CC group exhibited a significantly higher prevalence of preoperative elevated AFP levels (45.8% vs. 0, P < 0.001) compared with the ICC group. The two groups were comparable in terms of perioperative data. After a median follow-up of 34 months, there were no significant difference in 1-year OS (92% vs. 88%), 2-year OS (62% vs. 70%), 3-year OS (49% vs. 59%), 1-year RFS (46% vs. 58%), 2-year RFS (29% vs. 54%), 3-year RFS (29% vs. 42%) between the cHCC-CC and ICC groups (all P > 0.05). Conclusions The perioperative outcomes and long-term prognosis of LLR for patients with cHCC-CC are comparable to those observed in patients with ICC.